النِّظامُ الاشتقاقيُّ والمفرداتُ الإنتاجيَّةُ = The system of etymological derivation and the derived words = Sistem terbitan kata dan perbendaharaan kata produktif - Daud, Nadwah; Fauzi, Asma'; Mustapha, Nik Hanan (IIUM Press, International Islamic University Malaysia, 2017)
The system of etymological derivation of Arabic language is perfect, not least the verbs. For a student can easily make words using the basic letters with the system of derivation, particularly when the student is well-versed in the etymology. Therefore, the researchers ventured to study the process of derivation of words in the writing of a group of students who specialize the Arabic language and literature. The study further aims at exploring a general perception of its subjects towards the strategies that they employ to derive the words while writing. It also tries to find the influence of derivation process on them as a way of acquiring words and its development. The study has found that a majority of the subjects have been influenced with the system of derivation in the development of words with the course of time, in terms of abundance of the words, their varieties and their appropriate usage in the writing.